2020
DOI: 10.1177/1528083720934193
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical, thermal and sound absorption properties of flexible polyurethane foam composites reinforced with artichoke stem waste fibers

Abstract: Recently, due to environmental concerns and dependence on depleted resources, the use of renewable resources has become important in the preparation of various industrial materials. The use of natural fibers instead of petroleum-based synthetic fibers traditionally used in the production of composite materials provides many advantages in terms of both environmental and cost. The utilization of agricultural wastes as natural fibers also contributes significantly to the reduction and reuse of wastes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…They observed that 5% by fiber weight of treated fiber‐reinforced composite sample exhibits the best SAC in the 400–3200 Hz range. Olcay and Kocak 26 investigated the effect of treated artichoke stem waste fiber reinforcement on the SAC of PUF composites and observed an SAC of 0.98 at 2.4 kHz frequency for 5 wt% fiber reinforcement. Cherradi et al 27 presented the acoustic properties of composite specimens made from chemically processed alfa and sawdust wood fibers bonded with a polyvinyl binder.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that 5% by fiber weight of treated fiber‐reinforced composite sample exhibits the best SAC in the 400–3200 Hz range. Olcay and Kocak 26 investigated the effect of treated artichoke stem waste fiber reinforcement on the SAC of PUF composites and observed an SAC of 0.98 at 2.4 kHz frequency for 5 wt% fiber reinforcement. Cherradi et al 27 presented the acoustic properties of composite specimens made from chemically processed alfa and sawdust wood fibers bonded with a polyvinyl binder.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 23 studied ethylene propylene diene particles’ influences in the PU foams on sound absorption. Olcay and Kocak 24 prepared artichoke stem waste fibers reinforced PU bio-fiber composites. Baek and Kim 25 fabricated PU silicone-acrylic composites and examined the sound absorption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Artichoke fiber (AF) shows a lignin content (4.3%) similar to other fibers such as hemp and flax, whereas good mechanical properties with the help of its high cellulose content (75.3%), thus confirming its feasibility as reinforcement of polymer-based composites. 1215…”
Section: Introductionmentioning
confidence: 99%
“…Artichoke fiber (AF) shows a lignin content (4.3%) similar to other fibers such as hemp and flax, whereas good mechanical properties with the help of its high cellulose content (75.3%), thus confirming its feasibility as reinforcement of polymer-based composites. [12][13][14][15] In the past, NFs were used in constructing applications. Nowadays, NF have become valuable alternative elements to reinforce materials in the composite industry and have taken great interest in recent years because they allow the possibility of obtaining a new hybrid material for different applications.…”
Section: Introductionmentioning
confidence: 99%